Interleukin-17 plays a role in dental pulp inflammation mediated by zoledronic acid: a mechanism unrelated to the Th17 immune response? - Anna Clara Aragão Matos CARLOS; José Vitor Mota LEMOS; Marcela Maria Fontes BORGES; Maria Carolina Portela ALBUQUERQUE; Fabrício Bitu SOUSA; Ana Paula Negreiros Nunes ALVES; Thinali Sousa DANTAS; Paulo Goberlânio de Barros SILVA (University of São Paulo, 2023)
Abstract Objective To evaluate the influence of RORγT inhibition by digoxin on inflammatory changes related to interleukin-17 (IL-17) in the pulp of rats treated with zoledronate (ZOL). Methodology Forty male Wistar rats were divided into a negative control group (NCG) treated with saline solution, a positive control group (PCG) treated with ZOL (0.20 mg/kg), and three groups treated with ZOL and co-treated with digoxin 1, 2, or 4 mg/kg (DG1, 2, and 4). After four intravenous administrations of ZOL or saline solution in a 70-day protocol, the right molars were evaluated by histomorphometry (number of blood vessels, blood vessels/µm2, cells/µm2, total blood vessel area, and average blood vessel area) and immunohistochemistry (IL-17, TNF-α, IL-6, and TGF-β). The Kruskal-Wallis/Dunn test was used for statistical analysis. Results PCG showed an increase in total blood vessel area (p=0.008) and average blood vessel area (p=0.014), and digoxin treatment reversed these changes. DG4 showed a reduction in blood vessels/µm2 (p<0.001). In PCG odontoblasts, there was an increase in IL-17 (p=0.002) and TNF-α (p=0.002) immunostaining, and in DG4, these changes were reversed. Odontoblasts in the digoxin-treated groups also showed an increase in IL-6 immunostaining (p<0.001) and a reduction in TGF-β immunostaining (p=0.002), and all ZOL-treated groups showed an increase in IL-17 (p=0.011) and TNF-α (p=0.017) in non-odontoblasts cells. Conclusion ZOL induces TNF-α- and IL-17-dependent vasodilation and ectasia, and the classical Th17 response activation pathway does not seem to participate in this process.